PENGARUH CUSTOMER SATISFACTION DAN CUSTOMER TRUST TERHADAP CUSTOMER LOYALTY PRODUK KRIM PELEMBAB WAJAH FAIR & LOVELY - Dwi Wahyuni Rahma Wati; Naning Fatmawatie; Nilna Fauza (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
The industry is required not only to conduct business activities to obtain new customers, but also to increase the loyalty of old customers or customer loyalty. This study aims to determine customer satisfaction, customer trust, and customer loyalty. In addition, it is also to find out the effect of customer satisfaction on customer loyalty, the influence of customer trust on customer loyalty, and the influence of customer satisfaction and customer trust on customer loyalty on students of Islamic Boarding School ar-Roudloh Kediri City simultaneously on Fair & Lovely facial moisturizing cream products. This research uses a descriptive quantitative approach. The population of this research is 107 students of Islamic Boarding School ar-Roudloh Kediri City, East Java. While the number of samples in this study were 65 students. The results showed that the customer satisfaction, customer trust, and customer loyalty of each student included in the category of "Enough". From the results of correlation calculations it is known that partially customer satisfaction and customer trust variables have a positive and significant effect on customer loyalty of students of Islamic Boarding School ar-Roudloh Kediri on Fair & Lovely facial moisturizing cream products. The F test results show that Customer Satisfaction (X1) and Customer Trust (X2) simultaneously have a positive and significant effect on the Customer Loyalty (Y) variable with a value of 81.2%. While the remaining 18.8% is influenced by other variables such as choice reduction and habits, emotional bonding, and history with company.